A more economical choice for the cathode material of Ni-MH batteries with high electrochemical performances: 3D flower-like Ni–Fe LDHs. (15th December 2022) - Liu, Yana; Yu, Juanzhe; Jiang, Min; Hou, Jie; Zhu, Yunfeng; Zhang, Jiguang; Ba, Zhixin; Li, Liquan
Abstract: A series of 3D flower-like Ni–Fe layered double hydroxides (LDHs) were synthesized successfully and used as the cathode materials for nickel-metal hydride battery (Ni-MH battery). The 4Ni–Fe LDH electrode (Ni/Fe molar ratio = 4:1) displays the highest high-rate discharge property and the most excellent cycling performance. The discharge capacity of the 4Ni–Fe LDH electrode can reach up to 291.3 mAh/g at a discharge rate of 200 mA/g and which delivers a high capacity retention of 98.9% over 200 cycles. In contrast, the pure Ni(OH)2 electrode only has a capacity of 243 mAh/g, and after 100 cycles the capacity retention is just 73.4%. The above improvement can be ascribed to the formation of Ni–Fe LDHs which can consolidate the stability of α-Ni(OH)2 in the KOH solution. In addition, the unique flower-like morphology and the enlarged interlayer spacing also paly important role to promote ion transmission and charge transfer. Considering the competitive price of Fe, 3D flower-like Ni–Fe LDH may be a more economical choice for the cathode material of Ni-MH batteries. Highlights: A series of Ni–Fe LDHs with excellent electrochemical performances were prepared. The expanded interlayer space of LDH facilitates the transport of electrolyte ions. 3D flower-like structure increases the contact area of electrode materials and electrolyte. Ni–Fe LDH is a more economical choice for the cathode material of Ni-MH batteries.